1997
DOI: 10.1002/aic.690430225
|View full text |Cite
|
Sign up to set email alerts
|

Molecular thermodynamics of heat‐induced protein unfolding in aqueous media

Abstract: The molecular thermodynamic model studied is based on the two-state mechanism of inactivation, in which only native folded and polymorphous unfolded protein forms are present at equilibrium. The influence of solvent on protein stability is described in terms of perturbation of the protein distribution between the two conformational states. An expression derived for the chemical potential of the protein accounts for conformational changes, ideal mixing effects, and interaction of the protein with the surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
2
15
1
Order By: Relevance
“…In the case of ethanol addition, both ␣ and ␥ decrease, leading to a reduced driving force for hydrophobic aggregation. This general picture is consistent with experimental data on additive effects on protein stability (58)(59)(60).…”
Section: (D) Shown Is the Ratio P N͞supporting
confidence: 80%
See 1 more Smart Citation
“…In the case of ethanol addition, both ␣ and ␥ decrease, leading to a reduced driving force for hydrophobic aggregation. This general picture is consistent with experimental data on additive effects on protein stability (58)(59)(60).…”
Section: (D) Shown Is the Ratio P N͞supporting
confidence: 80%
“…Addition of ethanol has similar effects, but in the opposite direction. In both cases, changes in the asymptotic values (Ϸ5 dynes͞cm for 2 M NaCl and Ϸ30 dynes͞cm for 40 mol% ethanol solution) are consistent with experimental data on vapor-liquid surface tensions of their aqueous solutions (57,58). Further, we find that the EgelstaffWidom lengthscale, ␥ ϱ b , increases somewhat with salt addition and decreases with ethanol addition, consistent with our calculations.…”
Section: (D) Shown Is the Ratio P N͞supporting
confidence: 80%
“…The laser beam is attenuated through a series of neutral density filters and defocused using a long focal length lens to make the irradiance delivered to the sample approximately 15 mW/cm 2 . This relatively low-irradiance delivery is used to ensure that any protein unfolding is not due to thermal effects from the absorbed light [43] since heat is well known to denature proteins [44]. The solutions were exposed to increasing total energy doses of 0, 4.5, 13.5 and 27 J/cm 2 .…”
Section: Irradiationmentioning
confidence: 99%
“…These results suggest that sorbitol is preferentially excluded from the air-water surface, whereas glycerol is preferentially accumulated, i.e., it is surface active (Cioci, 1996). Air is relatively hydrophobic, hence we would expect sorbitol to be preferentially excluded from any hydrophobic patches on a globular protein's surface, whereas glycerol would be preferentially accumulated around these groups (Cioci, 1996;Cioci & Lavecchia, 1997). The surface of a globular protein is highly heterogeneous, consisting of functional groups of differing polarity, shape and size.…”
Section: Surface Tension Measurementsmentioning
confidence: 83%
“…Previous authors have indicated that surface tension measurements made at an air-cosolvent/solvent solution interface are correlated to the conformational stability of globular proteins (Cioci, 1996;Cioci & Lavecchia, 1997, 1998. A linear relationship has been observed between the thermal denaturation temperature (T m ) of some globular proteins and the surface tension of the cosolvent solutions in which they are dissolved, i.e., cosolvents that increase the surface tension tend to increase the T m of globular proteins (Cioci, 1996).…”
Section: Surface Tension Measurementsmentioning
confidence: 92%